2016
DOI: 10.1039/c6ra11405a
|View full text |Cite
|
Sign up to set email alerts
|

Albumin stabilized gold nanostars: a biocompatible nanoplatform for SERS, CT imaging and photothermal therapy of cancer

Abstract: Albumin stabilization of gold nanostars, which demonstrate high stability, biocompatibility, superior CT contrast, SERS and photothermal cytotoxicity towards cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…[5][6][7][8] Surface loading and orientation (or conformation) of surface ligands will alter signicantly the interaction these nanostructures with cells by changing the activity of these ligands, but is rarely considered for rationale design of these particles. [9][10][11] Currently, it is unclear whether protein-gold nanoparticle (AuNP) binding (capacity or conformation) at the nanoparticle surface are dependent on their radius of curvature. It has been suggested that, for spherical, citrate capped AuNPs, surface curvature alters the structure and binding capacity of adsorbed proteins onto their surface, although this issue remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Surface loading and orientation (or conformation) of surface ligands will alter signicantly the interaction these nanostructures with cells by changing the activity of these ligands, but is rarely considered for rationale design of these particles. [9][10][11] Currently, it is unclear whether protein-gold nanoparticle (AuNP) binding (capacity or conformation) at the nanoparticle surface are dependent on their radius of curvature. It has been suggested that, for spherical, citrate capped AuNPs, surface curvature alters the structure and binding capacity of adsorbed proteins onto their surface, although this issue remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the risk of radiation-induced damage makes it difficult to discern if cell death is caused by hyperthermia through the photothermal effect or by the laser itself. However, even though photothermal therapy works by killing a high percentage of malignant cells by itself, combined approaches including drug delivery and photodynamic therapy controlled by external stimuli provide added value to photothermal systems 36,110…”
Section: Biomedical Applications Of Albumin-aunpsmentioning
confidence: 99%
“…Another interesting system is that described by Sashidaran et al,110 where gold nanostars (AuNSs) were synthesized through a simple wet chemistry route and subsequently BSA-functionalized, yielding a stable monodispersed solution, with an average particle size of 120 nm. AuNS-BSA did not exhibit any inherent cytotoxic activity towards healthy (L929) and cancerous (KB) cells, but it showed significant photothermal ablation properties after laser exposure, thereby working as a therapeutic agent.…”
Section: Biomedical Applications Of Albumin-aunpsmentioning
confidence: 99%
“…hemolysis Assay: The in-vitro hemolytic property of ALg-Propolis NPs was studied by quantifying the free hemoglobin (Hb) released into plasma after lysis of red blood cells (RBC) upon interaction with nanoparticles (Sasidharan et al, 2016). Fresh blood was taken from the jugular vein of cattle into heparin containing tubes as an anticoagulant.…”
Section: Preparation Of Alginate-propolis Npsmentioning
confidence: 99%